2021
DOI: 10.1097/nne.0000000000001085
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Prelicensure Clinical Learning Experience

Abstract: Background: Studies of the clinical learning environment document the importance of the student's clinical learning process. Purpose: The aim of this study was to gather information on students' perceptions of their learning in the clinical environment. Methods: A mixed-method strategy was used to explore nursing students' (N = 194) perceptions of their clinical learning experiences. Data were collected using the Clinical Learning Environment Inventory (CLEI) survey and open-ended questions. Results:The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…(17,18) An additional study showed the importance of giving nursing faculty the background and helpful implementation techniques of student-centered learning. (19) Another study had students give feedback on preceptors, which is something that we have not done at our institution. (20) Students do have an exit interview that is completed with the student and perfusion clinical program director.…”
Section: Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…(17,18) An additional study showed the importance of giving nursing faculty the background and helpful implementation techniques of student-centered learning. (19) Another study had students give feedback on preceptors, which is something that we have not done at our institution. (20) Students do have an exit interview that is completed with the student and perfusion clinical program director.…”
Section: Descriptionmentioning
confidence: 99%
“…Previous studies in perfusion and allied health preceptor training have similar approaches with one study having 50 h of training and another study with five modules to complete [ 17 , 18 ]. An additional study showed the importance of giving nursing faculty the background and helpful implementation techniques of student-centered learning [ 19 ]. Another study had students give feedback on preceptors, which is something that we have not done at our institution [ 20 ].…”
Section: Descriptionmentioning
confidence: 99%